Pengaruh Hedonic Shopping Value dan Shopping Lifestyle terhadap Impulse Buying Konsumen X di Cikarang Utara - Ranuyoga Arsyiandi; Sarmin Sarmin (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study empirically examines the influence of hedonic shopping value and shopping lifestyle on impulsive buying behavior among X app users in North Cikarang area using quantitative approach and associative research design. The respondents of this study were 103 people selected through purposive sampling technique, while primary data were obtained through questionnaire distribution and then analyzed using multiple linear regression method using IBM SPSS version 26 software. The results of the analysis show that the hedonic shopping value variable is proven to have a significant contribution in influencing impulsive buying behavior, as evidenced by the calculated t-value of 4.703 which is greater than the t-table of 1.984 with a significance level of 0.000, far below the threshold of 0.05. In addition, the shopping lifestyle variable also shows a significant influence on impulse buying with a calculated t-value of 12.013, exceeding the critical value of the t-table at the same significance level. When both variables were tested simultaneously, the calculated F-value was 106.621, which far exceeded the F-table value of 3.09, thus strengthening the conclusion that hedonic shopping value and shopping lifestyle together have a strong influence on the tendency for impulsive buying behavior. Based on these findings, it can be concluded that the higher the hedonic drive that appears in consumer shopping activities and the stronger the consumptive lifestyle they lead, the greater the likelihood of consumers making spontaneous purchases on e-commerce platforms such as X. The results of this study also provide an illustration that digital consumer behavior in the modern era is strongly influenced by emotional and lifestyle factors, so understanding these aspects is important for e-commerce companies in formulating effective marketing strategies and being able to encourage a sustainable increase in transactions.